Effects of planting material and earthing-up on yield and yield contributing attributes of Mukhi Kachu - Faisal, SM; Salam, MA; Islam, MS; Hossain, MI (Bangladesh Journal of Agricultural Research, 2010)
An investigation was carried out at Agricultural Research Station, Pahartali, Chittagong during February to August 2002 to select suitable size of planting material and proper time of earthing-up to obtain higher yield of Mukhi Kachu. Three planting materials, primary corm (40g), half cut corm (20g), and secondary corm (10g) and four times of earthing-up, 1 month, 2 months, 3 months, and 4 months after planting were used. Different planting materials showed significant difference on weight of total corms/plot, weight of total cormels/plot and cormel yield. Different times of earthing-up showed significant effects on the parameters studied except no. of cormels/hill and weight of cormels/hill. The highest (3.71 t/ha) corm yield was obtained when primary corms were planted and earthing-up was done three months after planting. The combination of P1E ( primary corm x 3 months after planting) gave the highest (8.37 t/ha) cormel yield. Key Words: Mukhi Kachu; corm; cormel; planting material; earthing-up. DOI: 10.3329/bjar.v34i2.5798 Bangladesh J. Agril. Res. 34(2): 263-267, June 2009